2017
DOI: 10.3389/fimmu.2017.00936
|View full text |Cite
|
Sign up to set email alerts
|

Role of Different Subpopulations of CD8+ T Cells during HIV Exposure and Infection

Abstract: During HIV infection, specific responses exhibited by CD8+ T cells are crucial to establish an early, effective, and sustained viral control, preventing severe immune alterations and organ dysfunction. Several CD8+ T cells subsets have been identified, exhibiting differences in terms of activation, functional profile, and ability to limit HIV replication. Some of the most important CD8+ T cells subsets associated with viral control, production of potent antiviral molecules, and strong polyfunctional responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 117 publications
3
50
0
Order By: Relevance
“…However, compared with CD3 + CD20 – T cells, the expression of CD38 was decreased significantly on CD3 + CD20 + T cells. Although CD38 was also considered as one of the activation markers on T cells , studies on infectious diseases showed definitively that a subset of human T cells expressing HLA‐DR but not CD38 have a particularly high ability to suppress the virus . Given the increased expression of HLA‐DR on CD3 + CD20 + T cells, it was reasonable to assume that CD3 + CD20 + T cells represented an activated subpopulation and had a potential effector function in patients with psoriasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compared with CD3 + CD20 – T cells, the expression of CD38 was decreased significantly on CD3 + CD20 + T cells. Although CD38 was also considered as one of the activation markers on T cells , studies on infectious diseases showed definitively that a subset of human T cells expressing HLA‐DR but not CD38 have a particularly high ability to suppress the virus . Given the increased expression of HLA‐DR on CD3 + CD20 + T cells, it was reasonable to assume that CD3 + CD20 + T cells represented an activated subpopulation and had a potential effector function in patients with psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…showed definitively that a subset of human T cells expressing HLA-DR but not CD38 have a particularly high ability to suppress the virus [21,22]. Given the increased expression of HLA-DR on CD3 1 CD20 1 T cells, it was reasonable to assume that CD3 1 CD20 1 T cells represented an activated subpopulation and had a potential effector function in patients with psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…During acute viral infections, CD8+ T lymphocytes are able to control viral replication by producing cytokines and cytotoxic mediators 3,5 . However, when the infection becomes chronic, a persistent antigen exposure leads to the up-regulation of inhibitory receptors 3,5,12 . Also, at least in certain circumstances, it has been shown that the presence of inhibitory receptors may identify antigen specific chronically stimulated cells 16,17 .…”
Section: Polyfunctional Hiv-1 Specific Response By Cd8+ T Lymphocytesmentioning
confidence: 99%
“…It has been reported that the T CM cells of central long-term memory CD8 + T cells are derived from a subset of T EM cells, but the mechanism of this transformation is unclear 44,45 . Herein, we used vMIP-II studies to clearly demonstrate that the chemokine receptor-related phosphorylation pathway of effector CD8 + T cells is signi cantly down-regulated (but CCR7 pathway activation is still retained), and while inhibiting the apoptotic pathway, these molecular mechanisms affect the fate of effector CD8 + T cells, thereby increasing levels of central memory CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%